Finite Element Computation and Experimental Validation of Sloshing in Rectangular Tanks - Cruchaga-Ssa., M; Reinoso-Valenzuela, R (Springer Verlag, 2013)
Finite element computation and experimental validation of sloshing in rectangular tanks near the primary and secondary resonance modes are presented. In particular, 2D free-surface evolution is studied. The computational analysis is based on solving the Navier-Stokes equations of incompressible flows with a monolithic solver that includes a stabilized formulation and a Lagrangian tracking technique for updating the free surface. The time-dependent behavior of the numerical and experimental wave heights at different control points are compared, where the experimental data is collected using ultrasonic sensors and a shake table that controls the motion of the rectangular container. © 2013 Springer-Verlag Berlin Heidelberg.